ANALISIS BIBLIOMETRIK DENGAN VOSVIEWER: PENELITIAN KENYAMANAN TERMAL DAN EFISIENSI ENERGI MENGGUNAKAN CFD (Jurnal Arsitektur ARCADE, 2026)
Thermal comfort and energy efficiency in buildings are essential aspects in supporting sustainable development. This study aims to explore research patterns and map the relationships among topics related to thermal comfort and energy efficiency using a Computational Fluid Dynamics (CFD) approach. The method applied is a quantitative bibliometric analysis using data obtained from the Scopus database. Data collection was conducted using relevant keywords and limited based on publication years and subject areas. The analysis was carried out using VOSviewer to visualize publication trends, country contributions, and relationships among keywords. The results indicate that the number of publications increased from 2020 to 2026, with a peak occurring in 2024. China is identified as the country with the highest number of publications, followed by several other countries. The keyword mapping results reveal strong relationships among topics such as air temperature, airflow, ventilation systems, and indoor environmental conditions. The findings also indicate that research in this field is still dominated by technical, simulation-based approaches, particularly in the context of airflow and thermal parameters. This study is expected to serve as a reference for further research in improving building energy efficiency and thermal comfort.Keyword: Thermal comfort, energy efficiency, CFD